Exploring the Relationship among EFL Teachers’ Critical Thinking, Autonomy and Experience in Public and Private Schools - Mahzad Keyvanloo; Mohammad Reza Amirian; Marjan Vosoughi; Reza Bagheri Nevisi (Journal of Modern Research in English Language Studies)
The research delved into the connection between English Language instructors’ critical thinking, autonomy, and teaching experience among some public and private instructors. Two different sets of instructors including some private institute and high school instructors were selected from two major cities in Khorasan Razavi, Iran. The results from Path Analysis indicated that all subcomponents of instructors’ thinking critically except deduction could significantly predict instructors’ independence. Moreover, experience more effectively and remarkably predicted their independence. Accordingly, from among the five subcomponents of instructors’ CT, four sub-constituents were predicated by experience. Nevertheless, assessment and evaluation could not be properly predicted by experience. Findings also indicated that thinking critically could rightly and moderately be related to autonomy whereas there was a positively weak association between thinking critically and experience. Accordingly, findings pointed to a sizeable distinction between the two EFL settings regarding instructors’ autonomous behavior with non-public EFL instructors being more self-sufficient, selfdirected, and self-reliant than their counterparts in public high schools. In the same vein, there was no substantial distinction between the two settings concerning thinking critically.